Characterization of key astringent compounds and optimization of the fixation process of early tea in Chuanyu region - Wang, Xi; Liu, Yan; Wei, Fang; Guo, Xiaoyu; Cao, Shijie; Zeng, Liang; Luo, Liyong (NPJ science of food, 2025)
Due to inadequate fixation, early tea produced in the Chuanyu region exhibits high astringency. To mitigate the astringency of early tea, this study identified the astringent compounds present in the tea, subsequently optimized its fixation process based on the key astringent substances. Initially, 20 early tea samples were categorized into three groups (low, middle, and high astringency) according to the differences in astringency. Metabolomics revealed a total of 129 differential metabolites, of which 8 metabolites were positively correlated to the astringency of early tea. Finally, DoT (Dose-over-threshold: concentration-to-threshold ratio) values, taste recombination, omission, and addition experiments confirmed that (−) epigallocatechin (EGC), hyperin, and rutin were the key astringent compounds of early tea. Ultimately, the orthogonal test determined that the best fixation parameters of early tea were fixation temperature of 300 °C, fixation time of 65 s, and leaf amount of 150 kg/h, which significantly reduced the astringency of early tea.